Pros and cons of different therapeutic antibody formats for recombinant antivenom development. (May 2018) - Laustsen, Andreas H.; María Gutiérrez, José; Knudsen, Cecilie; Johansen, Kristoffer H.; Bermúdez-Méndez, Erick; Cerni, Felipe A.; Jürgensen, Jonas A.; Ledsgaard, Line; Martos-Esteban, Andrea; Øhlenschlæger, Mia; Pus, Urska; Andersen, Mikael R.; et al.
Abstract: Antibody technologies are being increasingly applied in the field of toxinology. Fuelled by the many advances in immunology, synthetic biology, and antibody research, different approaches and antibody formats are being investigated for the ability to neutralize animal toxins. These different molecular formats each have their own therapeutic characteristics. In this review, we provide an overview of the advances made in the development of toxin-targeting antibodies, and discuss the benefits and drawbacks of different antibody formats in relation to their ability to neutralize toxins, pharmacokinetic features, propensity to cause adverse reactions, formulation, and expression for research and development (R&D) purposes and large-scale manufacturing. A research trend seems to be emerging towards the use of human antibody formats as well as camelid heavy-domain antibody fragments due to their compatibility with the human immune system, beneficial therapeutic properties, and the ability to manufacture these molecules cost-effectively. Highlights: Comprehensive overview of reported antibodies against animal toxins. Pros and cons of antibody formats is discussed. Pharmacokinetics and pharmacodynamics of antibodies and their fragments. Trends in recombinant antivenom development are presented.